Evaluation of Taste Related Genes (CD 36, SHH, PLCß2) Expression in Saliva - Ozturk, Elif Esra; Dikmen, Derya (Progress in Nutrition, 2021)
Due to its non-invasiveness accessibility and high availability in diagnostic and prognostic evaluation, the use of saliva has gradually gained popularity in recent years. This study's objective was to examine the expression level of taste-related genes in saliva (SHH, CD 36, PLCß2). The study was carried out in two stages. In the first stage, both lemon-juice stimulated and unstimulated saliva was gathered from 10 participants (6 males and 4 females) to examine the effect of stimulation with citric acid on expression level. Forty-six subjects (22 males, 24 females) participated in the second stage, and unstimulated saliva was collected due to the quality and yield of the mRNA obtained to examine the expression level of taste-related genes (SHH, CD 36, PLCß2). There was no difference between SHH expression levels in saliva stimulated with lemon juice and unstimulated saliva. The results showed that, SHH, CD 36, PLCß2 expression was higher in unstimulated saliva (p>0.05). The study demonstrated that unstimulated saliva is more suitable for determining taste-related gene expression levels.